1996
DOI: 10.1093/treephys/16.4.417
|View full text |Cite
|
Sign up to set email alerts
|

Carbon assimilation and water-use efficiency by neighboring Mediterranean-climate oaks that differ in water access

Abstract: Carbon assimilation and water-use efficiency by neighboring Mediterranean-climate oaks that differ in water access. To assess how carbon uptake and water-use efficiency (WUE) are affected by water access, I monitored leaf and canopy gas exchange of neighboring Q. durata and Q. agrifolia trees over a 15-month period. Transpiration and photosynthesis by Q. agrifolia peaked in spring and declined through the summer, whereas transpiration and photosynthesis by Q. durata continued at a moderate rate year round. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 29 publications
7
40
2
Order By: Relevance
“…The distribution of root systems may also have an effect on the sensitivity of sap flow responses to soil-water change [31,[54][55][56][57]. Most of these studies showed that inherently shallow rooted species may show large reductions of sap flow or conductance in response to VPD as the soil dries, while deeply rooted species may maintain moderate rates of transpiration regardless of soil moisture.…”
Section: Response Of Sap Flow To Meteorological Factors Under Differementioning
confidence: 99%
“…The distribution of root systems may also have an effect on the sensitivity of sap flow responses to soil-water change [31,[54][55][56][57]. Most of these studies showed that inherently shallow rooted species may show large reductions of sap flow or conductance in response to VPD as the soil dries, while deeply rooted species may maintain moderate rates of transpiration regardless of soil moisture.…”
Section: Response Of Sap Flow To Meteorological Factors Under Differementioning
confidence: 99%
“…We also recorded sums of evaporation that were lower than transpiration values for evergreen oak savanna growing on the coastal range of California (Goulden, 1996); a landscape of Quercus agrifolia transpired 443 mm and Q. durata transpired 570 mm in a year. Evergreen oaks in northern California grow in a wetter and cooler climate and access ground water (Griffin, 1988) which limits the degree of stomatal closure during the summer.…”
Section: Evaporation and Sensible Heat Exchange: Temporal Dynamicsmentioning
confidence: 99%
“…For example, predictions of potential evaporation rates with radiation-based models, such as the Priestley-Taylor equation (Priestley and Taylor, 1972), severely overestimate evaporation of savanna woodlands (Major, 1988;Lewis et al, 2000). This occurs because a semi-arid climate limits the amount of leaf area that can be sustained by the ecosystem (Eagleson, 1982;Baldocchi and Meyers, 1998;Eamus and Prior, 2001;Eamus, 2003) and drying soils force stomatal closure, which limit transpiration when evaporative demand is greatest (Kelliher et al, 1993;Goulden, 1996;Kiang, 2002).…”
Section: Canopy Conductance and Photosynthesismentioning
confidence: 99%
“…Daily transpiration is correlated to soil moisture during short drying periods and seasonally [11,14,20,43,46,57,58]. Granier and Loustau [23] showed that increasing soil moisture deficit during 8 d resulted in a decrease in E C of maritime pine to a sixth of the initial value.…”
Section: Canopy Transpirationmentioning
confidence: 99%